2019
DOI: 10.1002/aur.2241
|View full text |Cite
|
Sign up to set email alerts
|

ASD symptoms in toddlers and preschoolers: An examination of sex differences

Abstract: Although considerable work has documented higher prevalence rates of autism spectrum disorder (ASD) in boys, fewer studies have focused on sex differences within samples of young children at‐risk for ASD. This study examined sex differences in ASD symptom domains and ASD screening outcomes among toddlers (18–35 months) and preschoolers (36–72 months) with ASD‐related concerns. Participants included 480 children between 18 and 72 months evaluated by university‐based ASD specialty clinics. Results revealed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Additionally, despite the fact that the tools and techniques for assessment have been refined over time, a portion of girls with higher cognitive and language abilities are at risk of not being identified until later in life (18,(20)(21)(22). A population-based study in the UK showed that females with similar levels of symptom expression to males were less likely to receive a diagnosis of ASD from clinical services (23). Moreover, boys are usually detected by ASD screeners at higher rates than girls, although sex differences in screening scores are not as pronounced (24,25).…”
Section: Sex Difference In Core Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, despite the fact that the tools and techniques for assessment have been refined over time, a portion of girls with higher cognitive and language abilities are at risk of not being identified until later in life (18,(20)(21)(22). A population-based study in the UK showed that females with similar levels of symptom expression to males were less likely to receive a diagnosis of ASD from clinical services (23). Moreover, boys are usually detected by ASD screeners at higher rates than girls, although sex differences in screening scores are not as pronounced (24,25).…”
Section: Sex Difference In Core Symptomsmentioning
confidence: 99%
“…Most males are fascinated by toys on wheels or screen time (e.g., video games), while girls mostly show obsessions with random objects (e.g., stickers, stones, pens, animals) and play obsessive and repetitive games with other toys (16,38). Differences in core ASD symptoms may become more pronounced as individuals age and cultural influences play a larger role into gender differences (23) leading to inconsistent and conflicting results. In addition, the difference in core symptoms could be also related to the change in intervention strategies that occur between toddlerhood to preschool-school age period partly due to transition from "early home based" intervention to "school-based" (23).…”
Section: Sex Difference In Core Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other studies found worse social skills in girls (Hartley and Sikora, 2009;Lawson et al, 2018). Moreover, while a recent study by Ros-Demarize et al (2020) reported that females demonstrated greater deficits in social communication, with similar results in both parental reports and standardized observations, a previous study by Mandy et al (Mandy et al, 2012) showed differences in how parents and teachers, who are often the first to recognize potential autistic traits, evaluate social skills. In the latter research, while parents reported an equivalent impairment in social and communication areas in both sexes/genders, teachers more often recognized social difficulties in males since they showed more externalizing problems than females.…”
mentioning
confidence: 84%
“…In the last few years, sex-related alterations in the clinical presentation of autism spectrum disorder (ASD) among preschool-age children have been described by many investigators [ 3 , 4 ]. However, some studies did not find sex-related differences [ 5 ] or observed behavioral alterations between boys and girls with ASD that were different from those generally described [ 6 ]. The sex differences in the clinical presentations of ASD also point to the possible need to use different tools in the diagnosis of ASD for boys and girls, or at least different diagnostic scores when using the same tools for boys and girls [ 7 ].…”
Section: Introductionmentioning
confidence: 92%